2021
DOI: 10.1111/jsr.13375
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea in airline pilots during daytime sleep following overnight flights

Abstract: To identify the vulnerability of recovery sleep, this study investigated the occurrence of obstructive sleep apnea during daytime sleep following overnight flights in healthy airline pilots. We conducted daytime polysomnography following a long-haul nighttime flight in 103 pilots. The following variables were assessed: apnea-hypopnea index, respiratory disturbance index and oxygen desaturation index. Moderateto-severe obstructive sleep apnea was defined as an apnea-hypopnea index ≥15. Seventy-three pilots (70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Occupational physicians should inform airline pilots about proper sleep habits as well as on the relationships between sleep disorders, fatigue, and depression [4][5][6][7][8][9][10][11]. Current health surveillance activities should also include adequate screening programs for sleep disorders and OSA.…”
Section: Reducing the Risk Of Sleep And Mental Health-related Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational physicians should inform airline pilots about proper sleep habits as well as on the relationships between sleep disorders, fatigue, and depression [4][5][6][7][8][9][10][11]. Current health surveillance activities should also include adequate screening programs for sleep disorders and OSA.…”
Section: Reducing the Risk Of Sleep And Mental Health-related Problemsmentioning
confidence: 99%
“…In a study by Alhejaili et al [ 8 ], OSA was identified by home sleep testing in 69% of Saudi-based airline pilots. On analyzing 103 pilots after a long-haul night-time flight using daytime polysomnography, Han et al [ 9 ] found that 73 (70.9%) had moderate-to-severe daytime OSA despite no known previous history. Elevated body mass index and cumulative flight time were identified as independent predictors [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although such an effect has not been widely described in clinical studies related to anaesthesia, night-time work has been shown to be associated with increased morbidity in other work settings. 6 Recent data also suggests that anaesthesiologists believe the current conditions of their night-time practice adversely affect their professional performance, the safety of their patients, and their own quality of life. 7 Many countries have adopted the European Working Time Regulations, thus showing an interest in providing organisational support to night-time workers.…”
Section: Introductionmentioning
confidence: 99%
“…Night-time work is also probably accompanied by poorer healthcare professional well being. Although such an effect has not been widely described in clinical studies related to anaesthesia, night-time work has been shown to be associated with increased morbidity in other work settings 6 . Recent data also suggests that anaesthesiologists believe the current conditions of their night-time practice adversely affect their professional performance, the safety of their patients, and their own quality of life 7 …”
Section: Introductionmentioning
confidence: 99%